2014
DOI: 10.3748/wjg.v20.i42.15797
|View full text |Cite
|
Sign up to set email alerts
|

Immediate detection of endoscopic retrograde cholangiopancreatography-related periampullary perforation: Fluoroscopy or endoscopy?

Abstract: ERCP-related perforations may be difficult to diagnose by video endoscope and digital fluoroscope detection of retroperitoneal free air or contrast medium leakage can facilitate diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
0
10
1
2
Order By: Relevance
“…It is therefore not surprising to see that all of our patients in the fluid‐alone group were diagnosed after the procedure and has more time elapsed before the diagnosis. While it is well documented that early perforation diagnosis is associated with better prognosis, in our study, we found that although all the patients in the fluid‐alone group were diagnosed late, most of them only required medical treatment and had a shorter mean hospital stay than those in the air‐fluid group. We thus suggest that, in addition to early diagnosis, the prognosis of an ERP depends on the location and the size of the perforation.…”
Section: Discussioncontrasting
confidence: 61%
“…It is therefore not surprising to see that all of our patients in the fluid‐alone group were diagnosed after the procedure and has more time elapsed before the diagnosis. While it is well documented that early perforation diagnosis is associated with better prognosis, in our study, we found that although all the patients in the fluid‐alone group were diagnosed late, most of them only required medical treatment and had a shorter mean hospital stay than those in the air‐fluid group. We thus suggest that, in addition to early diagnosis, the prognosis of an ERP depends on the location and the size of the perforation.…”
Section: Discussioncontrasting
confidence: 61%
“…Traditionally, an early or immediate diagnosis of ERCP-related perforation has depended mostly on the use of either video endoscopy or digital fluoroscopy. 2 In the cases described by Kumbhari et al, the intraprocedural detection rate of duodenal perforation is approximately 10%, which we believe is too low. This implies that only a small portion of the included patients received immediate diagnoses of ERCP-related perforation under fluoroscopy or duodenoscopy.…”
mentioning
confidence: 66%
“…If the result of the "safety injection" is normal, then no further intervention is necessary because the patient may have a Stapfer type IV perforation, which does not require therapy. [2][3][4]…”
Section: Responsementioning
confidence: 99%
See 1 more Smart Citation
“…A C-vision Safire or Sonialvision Safire digital fluoroscope (Shimadzu Corporation, Kyoto, Japan) and a JF-260 or TJF-240 video endoscope (Olympus, Tokyo, Japan) with CO 2 instead of standard air insufflation were used in all procedures [22].…”
Section: Endoscopic Retrograde Cholangio-pancreatography and Peroral mentioning
confidence: 99%